Analisis Perbandingan Integrasi Data Antara BSI Mobile dengan Byond By BSI dalam Meningkatkan Kemudahan Transaksi Perbankan - Dwi Septianingrum; Ansory Ramadhan; Ratna Hasibuan; Nurbaiti Nurbaiti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the comparison of features and data integration between two mobile banking applications by Bank Syariah Indonesia, namely BSI Mobile and BYOND by BSI, in enhancing banking transaction convenience. The research method employed is descriptive qualitative through a literature review from various relevant sources. The results show that BYOND by BSI adopts a more modern data integration system using microservices architecture and open APIs, thus providing better transaction convenience and security compared to BSI Mobile, which still relies on a centralized system. Innovative features such as biometric authentication, QRIS, and a more intuitive user interface further enhance the digital banking experience for customers. However, BYOND by BSI still faces performance challenges, particularly in transaction speed, as the application experiences delays (lag) in several features that may reduce user comfort. The study concludes that BYOND by BSI is superior in facilitating banking transactions compared to BSI Mobile. It is recommended that future research be conducted using a quantitative approach to directly evaluate user experience in a more comprehensive manner.